Reconfigurable OFDM systems - Nolan, Keith E. (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2005)
Orthogonal Frequency Division Multiplexing (OFDM) is a multi-carrier wireless transmission technique. OFDM is used for robust, high quality and high data-rate music, voice, images, video, news and data broadcasts. It is also used for high data-rate Wireless Local Area Network (WLAN) communications links, and is expected to play an important part in emerging and future wireless communications schemes and devices. OFDM uses many carrier frequencies in unison, each transmitting a section of an input data sequence. This operation enables OFDM to achieve its high-data rate capabilities. The carrier frequencies may be spaced as close together as is theoretically possible, yet they do not interfere with one another. These carrier frequencies are known as orthogonal carriers. OFDM is more robust than single-carrier transmission systems in a multi-path fading channel environment due to its frequency-diversity and transmission structure characteristics.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin